Active biomonitoring in streams by using multimarker approaches of mussels - T. Ukasha; N.U.H. Faisal; B.K. Adji; A.P. Nugroho (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Streams that pass through densely populated areas and business and industrial centers are continuously threatened by various pollutants, including metals and microplastics, originating from dispersed sources. Biomonitoring is necessary to evaluate the health of stream ecosystems, considering that streams are essential ecologically and for human life. A biomonitoring approach through multimarkers can provide a comprehensive picture of the condition of stream ecosystems. It can identify biomarkers that are sensitive and specific to the presence of certain types of pollutants. This study evaluates the ecosystem health of Code Stream, Yogyakarta, Indonesia, through active biomonitoring by transplanting mussels Anodonta woodiana into cages at three stations, representing mild (station 1), moderate (station 3), and severe (station 2) polluted ecosystem conditions based on human activities around the stream.METHODS: The mussels were transplanted into the Code Stream. Then, on days 0, 3, 7, 14, 21, and 28, the organisms were taken, and their gills and mantle were dissected in the laboratory. The organs were analyzed for microplastic accumulation and characteristics, copper concentration, superoxide dismutase, catalase, acetylcholinesterase activities, metallothionein concentration, and deoxyribonucleic acid damage. Biomarkers sensitive to pollutants were evaluated by integrated biomarker response. The combined effects of the complexity of environmental factors on the biomarkers were analyzed by multiple-factor analysis.FINDINGS: The Code Stream waters at all stations were polluted with microplastics and copper. The increase in the two pollutants in the mussel organs was a function of time, with no differences among stations. The abundance of microplastics and copper concentrations in the water was closely related to their accumulation in both organs. Exposure to various contaminants in the stream strongly increased the superoxide dismutase and catalase activities in both organs at the beginning of exposure in all stations, with the highest being at station 3. The acetylcholinesterase activity was strongly inhibited in the gills at station 2. The metallothionein concentration slightly increased, and the highest increase occurred in the gills at station 2. The deoxyribonucleic acid damage was more intense at stations 2 and 3. Integrated biomarker response analysis showed that deoxyribonucleic acid damage, catalase activity, and metallothionein concentration were biomarkers responsive to stream pollution. Multiple-factor analysis revealed that superoxide dismutase, catalase, and acetylcholinesterase activities were biomarkers that indicated the environmental pollution of Code Stream waters. Multimarker analysis confirmed that the pollution level at stations 2 and 3 was higher than at station 1.CONCLUSION: Active biomonitoring can offer a more accurate and comprehensive view of the time-dependent link between exposure and biomarker response. This active biomonitoring strategy identified sensitive and specific biomarkers for the presence of metal and pesticide contaminants in stream ecosystems. The pollution of Code Stream waters harms oxidatively stressed mussels and may endanger human health via the food chain. This work contributes substantially to understanding pollution exposure and its effect on mussels. It develops pollution-sensitive biomarkers for routine stream health monitoring. Mitigation activities involving diverse stakeholders and public education on sustainable management efforts must continue to achieve sustainable development.